Measuring Effectiveness of SMART Patrol in Biodiversity Protection of Rimbang Baling and Bukit Betabuh, Sumatra - Fardilla, Antika; Novarino, Wilson; Widodo, Febri Anggriawan; Hendra, Jon; Aadrean (Institut Pertanian Bogor (IPB University), 2024)
The main authorities and practitioners face crucial challenges in safeguarding wildlife and conservation areas due to massive direct anthropogenic disturbances, such as illegal logging, habitat conversion into human development areas, and wildlife poaching. Therefore, measuring the effectiveness of wildlife and habitat protection is essential for wider conservation intervention. This study aimed to examine patrol effectiveness using measurable effort and parameters of SMART-based data collection in Rimbang Baling and Bukit Betabuh, Sumatra. We conducted a series of planned SMART-based data collections in designated patrol blocks of Rimbang Baling from 2014 to 2018. We implemented catch per unit effort (CPUE) measurement by the number of detected illegal activities and then a generalized linear model (GLM) to assess the relationship between patrol efforts and threat numbers. This study covered 209 patrols within 2,129 patrol days, 13,153.05 patrol hours, and 14,864 km. The CPUE value decreased from 0.381 to 0.191. Our GLM showed that patrol efforts significantly reduced threat numbers. This study provides new knowledge regarding SMART-based data collection and its ability to increase the effectiveness of patrols in promoting better protection and threat reduction in conservation areas in Indonesia.